Review of Industry 4.0 Strategy and Organization Readiness Level of Automotive SME’s in Indonesia - Ishardita Pambudi Tama; Ceria Farela Mada Tantrika; Dewi Hardiningtyas; Effendi Mohamad (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
The focus of Industry 4.0 concept is to integrate production, information technology and the optimal usage of internet. It includes set of tools and applications that utilizing a smart embedded system of machines to perform a certain level of autonomous tasks in industrial system. The ideal infrastructure to perform such concept is remain a big challenge, especially for Small and Medium Enterprises (SMEs). In order to develop strategies which SMEs can get the maximum benefit from Industry 4.0, this study aims to measure their readiness level to adopt the concept. This study was conducted to fill the gap in such area of study, by adopting the “Industrie 4.0 Readiness model” by VDMA. Using survey and interview from 57 SMEs in Indonesia. Various data related with current state of knowledge and strategy implementation of Industry 4.0 were collected. The study concluded that most of the SMEs beyond the sample (56%) were still in the beginner level of adoption, 14% were even in the outsider level, and the rest of them still had no plan for the implementation. This data shows us that the implementation and adoption of Industry 4.0 in SMEs in Indonesia is still at the beginning, which need more attention from the policy and strategy maker to get to more mature level.